2018
DOI: 10.24127/bioedukasi.v9i2.1614
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH EKSTRAK ETANOL DAUN TAPAK DARA (Catharanthus roseus L.) DAN KOLKISIN TERHADAP PERKECAMBAHAN BIJI CABAI RAWIT HIBRIDA (Capsicum annuum)

Abstract: Catharanthus roseus L. contain vinca alkaloid compounds which have anti-mitotic effect like colchicine. The application of Catharanthus roseus L. extract and colchicine in many plants was usually done by soaking the plant seeds. The aim of this research was to analyze the effect of ethanolic leaf extract of Catharanthus roseus L. and colchicine on seed germination of Capsicum annuum. 20 Seeds of Capsicum annuum were soaked for 24 h in ethanolic leaf extract of Catharanthus roseus L. (0,05%, 0,1% dan 0,5%), col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…With depolymerization, the spindle thread formation is inhibited. Consequently, the chromosomes fail to divide during mitosis but continue to multiply (Purbosari and Puspitasari, 2018). Therefore, it is a polyploidization process.…”
Section: Resultsmentioning
confidence: 99%
“…With depolymerization, the spindle thread formation is inhibited. Consequently, the chromosomes fail to divide during mitosis but continue to multiply (Purbosari and Puspitasari, 2018). Therefore, it is a polyploidization process.…”
Section: Resultsmentioning
confidence: 99%
“…These alkaloids have a colchicine-like effect that can duplicate chromosomes. They act by preventing tubulin polymerization, so that the separation of chromosome sets is disrupted when mitosis and cells have multiplied the chromosomes (Purbosari and Etika, 2018). Currently, the antimitotic compounds vincristine and vinblastine are available in the form of pure compounds and are produced commercially (Daryono, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous studies conducted on vinca alkaloids-induced polyploidy in order to improve the characters and yields of plants. Soybean (Kusnuriyanti et al, 2017), melon (Daryono et al, 2018), cayenne pepper (Purbosari and Etika, 2018), lily (Wardana et al, 2019), and spearmint (Viza, 2019) showed significant increase in several characteristics such as plant height, leaf area, fruit size, and seed weight. Therefore, the present study was carried out to investigate the mutagenic effect of vinca alkaloids on morphological traits in jack beans.…”
Section: Introductionmentioning
confidence: 99%